PROFIL TINGKAT KEBUGARAN JASMANI ATLET TAEKWONDO KYOURUGI PEMULA DOOJANG BARCELONA TRAINING TAEKWONDO CENTER SELAMA PANDEMI COVID – 19 DI PEKANBARU - Thasya Marta Ningsih; Ramadi Ramadi; Alimandan Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the profile of physical fitness level, especially the taekwondo kyourugi beginner athlete in doojang Barcelona Training Taekwondo Center during the covid-19 pandemic in Pekanbaru. This research uses descriptive quantitative research; this research will have 12 athletes for population and use total sampling technique. Based on the results of the research, the level of physical fitness of taekwondo kyourugi beginners athlete in doojang Barcelona Taekwondo Center Training in detail is: 0 athletes (0%) have very good physical fitness, 2 athletes (0.17%) have good physical fitness, 7 athletes (0.58%) have moderate physical fitness, 2 athletes (0.17%) have poor physical fitness, and 1 athlete (0.08%) have very poor physical fitness. Based on the results of the study, it was shown that the taekwondo kyourugi beginner athlete at the Barcelona Training Taekwondo Center had moderate physical fitness.Key Words: Physical fitness level profile, athlete, doojang barcelona trainingtaekwondo center.